Use Of Thematic English Textbook In Teaching English To PGSD Students At Jambi University - Saharudin; Harsyah, Ahmad Syauqi; Handayani, Reli; Putri, Regita Riani; Hermanetty (Journal of Classroom Action Research, 2024)
English as Foreign Language course is offered in the primary school teacher program, though it is a compulsory subject at Jambi University. In practice, there is no standardized English material used in this program. Therefore, implementing English material relevant to the field becomes a necessity and thematic English textbook can be an alternative. This study is aimed to investigate the use of the thematic English textbook in teaching English to PGSD students at Jambi university. This study employs classroom action research and qualitative approach to analyze the data. To collect the data the researcher used techniques proposed by Mills (2003) such as archival sources: notes during lectures, average attendance, number of students subject to sanctions, discipline. Journal: Daily observational notes and artifacts such as sitting position, video recording, student portfolio.  The finding shows that the students enjoy the material since the topic discussed are familiar. Besides, the material is proved can encourage students’ active participation during teaching and learning process. To conclude, the implementation of thematic English textbook can be an option in maximizing student’s potential.